The Influence of Hedonic Shopping Value and Fashion Involvement on Impulse Buying at Tunjungan Plaza Mall, Surabaya City - Muhammad Nashir Hasan; Rizky Dermawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to find out how hedonic shopping value and fashion involvement influence impulse buying at the Tunjungan Plaza mall, Surabaya City. This research method is quantitative by taking a sample of 100 respondents which is determined based on the sampling technique based on guidelines according to Ghozali. The population in this study were visitors to the Tunjungan Plaza Surabaya mall. While the sample in this study was taken using convenience sampling. The sample consists of respondents who have made impulse purchases at the Tunjungan Plaza mall, Surabaya City. The data used in this study are primary data and secondary data. The analysis technique used in this research is (PLS) with validity test, reliability test and hypothesis test. The results of this study prove that: (1) Hedonic Shopping Value has a positive and significant effect on Impulse Buying. (2) Fashion Involvement has a positive and significant effect on Impulse Buying.